THE CONCEPT, ESSENCE, AND STAGES OF DEVELOPMENT OF CREATIVE THINKING (International journal of artificial intelligence, 2026)
The article provides a comprehensive analysis of the concept, essence, and developmental stages of creative thinking. In the modern educational paradigm, creative thinking is no longer viewed as an innate talent but as a systematic cognitive skill that can be cultivated. This study explores the psychological and pedagogical foundations of creativity, emphasizing its role in problem-solving and innovation. By analyzing various theoretical models, the author identifies the key phases of creative development, from initial perception to the practical realization of ideas. The findings highlight the importance of creating a conducive environment for fostering creative cognitive processes in students, ensuring their adaptability in a rapidly changing global landscape.